Legacies of the Past and the American Family: Sam Shepard’s True West and Suzan-Lori Parks’s Topdog /Underdog - Németh, Lenke (FOCUS: Papers in English Literary and Cultural Studies, 2018)
Isolation from societal and historical continuity ingrained in American thought and culture has resulted in an unprecedented economic growth, creativity, and flexibility in all facets of American life. Paradoxically, a constant search for an American past—generated by the lack of a common history—also prevails in American culture and these mutually exclusive trends lead to a sense of “rootlessness, loss of connections, and anxiety about identity” (Menides 607). American literary expressiveness appears to reflect these opposing views on history as well as the impact these attitudes exert on the (in)stability of the American character. Viewed from the “classic” period of American literature a variety of responses were generated by the literary culture. American writers’ approaches to history range from evident separation from the constraints and restraints of history and tradition (Emerson, Thoreau) through creating romanticized versions of the American past (Cooper, Longfellow) to the search of a “usable past”2 (Eliot, Pound) that would explain the causes and impinge on the way how Americans exist in the present (Menides 607).